The Impact of Covid-19 on Romanian Entrepreneurs in Relation to the Use of Digital Marketing Strategies - Elena Florentina GREJDAN; Elena GOGA; Iasmina-Iulia GRĂDINESCU; Gheorghe ORZAN (Communications of International Proceedings, 2021)
Coronavirus disease (COVID-19) is an infectious disease caused by a newly discovered coronavirus. It was discovered on December 12, 2019, in China. On January 22, 2020, the first cases of COVID-19 infection on Romanian territory were confirmed. Then, in March 2020, a state of emergency was declared in Romania. From that moment on, the pandemic began to affect the economy, implicitly the entrepreneurial environment. The scope of the present paper is to reveal the impact of COVID-19 on Romanian entrepreneurs in the context of the pandemic situation. The research method involves a quantitative investigation with an exploratory-descriptive scope. The sample consisted of 300 participants of the entrepreneurial field. Compared to other articles that have analysed this idea, our main objectives were to analyse the tendency of entrepreneurs to implement new business strategies, if they predicted a decrease in turnover and the tendency of the entrepreneurial environment to invest in digital marketing strategies. The aim of the study is to illustrate that the general trend of the entrepreneurial field is one of growth. Following the analysis of the results, one may observe that Romanian entrepreneurs have learned from the effects of the restrictions imposed in 2020. Respectively, they learned to be flexible and to adapt their business and marketing strategy even in times of crisis. So, now they have the experience of last year and most of them have optimistic forecasts for the future.
Keywords: Digital Marketing; Entrepreneurship; Covid-19; Global Health Crisis; Economy; Business